Small Intestinal Bacterial Overgrowth in Various Specialties of Medical Practice (Literature Review and Expert Council Resolution) - V. T. Ivashkin; V. V. Fomin; O. N. Tkacheva; O. S. Medvedev; E. A. Poluektova; D. I. Abdulganieva; S. R. Abdulkhakov; O. P. Alexeeva; S. A. Alekseenko; D. N. Andreev; A. Yu. Baranovsky; M. S. Zharkova; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to discuss current views on the clinical significance, diagnostic opportunities, and therapeutic approaches in the treatment of small intestinal bacterial overgrowth (SIBO) as an important component in the gut microbiota function assessment, to assess the awareness of physicians and the opportunities in the diagnosis and treatment of this disease in patients in the Federal districts of the Russian Federation, as well as to present the proceedings of the Expert Council held on December 16, 2023 in Moscow.Key points. SIBO is a common syndrome often associated with irritable bowel syndrome, liver cirrhosis, asthma, and congestive heart failure, being also a predictor of early death in the elderly. Today, in many regions of the Russian Federation, there are limitations for instrumental diagnosis of this disease — lack of awareness among doctors, unavailability of gas analyzers for diagnosing SIBO, lack of information about the need to diagnose SIBO in the standards of compulsory health insurance. Rifaximin is the first-line treatment due to the highest therapeutic efficacy. One of the ways to increase the efficacy of SIBO treatment is to include strain-specific probiotics in the treatment regimen. Saccharomyces boulardii CNCM I-745 is thought to be the most studied, promising probiotic. The review also presents statistical data on the issues in the diagnosis and treatment of SIBO in the regions of the Russian Federation.Conclusion. Optimization of approaches to the diagnosis and treatment of SIBO, the development of domestic gas analyzers, increasing the awareness of physicians in all regions of the Russian Federation, as well as the development and optimization of clinical recommendations appear to be necessary measures to increase the effectiveness of medical care, the duration and quality of life of the Russian population. These goals can be achieved within the framework of Federal programs under the supervision of specialized reference centers of the Ministry of Health of the Russian Federation.